Características morfometricas, merísticas, físicas y químicas del pescado ratón silvestre (Leporinus ecuadorensis) en la zona de Babahoyo-2017. - Triviño Bravo, Josselin Lisseth (2017)
In order to study the morphometric, meristic, physical and chemical characteristics of the wild mouse (Leporinus ecuadorensis), this work was carried out in the Babahoyo River, where 250 specimens of Leporinus e., Which had a weight range of 75- 175 g, these were transported to the meat plant of the "La María" Campus of the Quevedo State Technical University where data of their weight, morphometric characteristics were taken; Total length (LT), head width (LC1), trunk width (LC2), tail width (LC3), perimeter of head (P1), body perimeter at the first radius of the dorsal fin ( P2) and perimeter at the first radius of the anal fin (P3) for which frequency analysis was performed, a descriptive statistic was applied for physical-chemical and mineral analyzes. The morphometric variables evaluated showed a strong correlation with fish weight (r^2= 0.80) except LT (r^2= 0.43), Leporinus e. Showed a protein content of 22.08% and a low fat content of 4.68%, which is considered to be within the group of average fat species. The results of the physical analyzes carried out are a bluish meat and present low losses of water by dripping and cooking (4.69 and 19.95% respectively) compared to other species.